The Effect Of Holcim Cement Substitution On Fine-Grained Soils Its Influence On The Stability Of Soil Bearing Capacity Using The Terzaghi Method And Meyerhoff Method - Sujatmiko, Heri (Malikussaleh University, Aceh, Indonesia, 2023)
Soil is vital as a construction material and load support in civil engineering building work. The aim of stabilization itself is to increase the bearing strength of the soil by increasing soil cohesion and friction angles in the soil and maintaining good soil bearing strength so that it does not experience a decrease due to the influence of weather and air. Based on the Unified classification system, it is included in the OH classification or what is usually called clay soil with high organic plasticity, while based on the ASSHTO classification, the soil in Pancoran Village, Glagah District, Banyuwangi Regency is included in group A-7-5(25). The addition of Holcim Cement to clay soil from the Pancoran Village area, Glagah District, Banyuwangi Regency in the Direct Shear test obtained the most significant value in the 8.5% mixture with a curing time of 9 days for the ? value, namely ? = 19.8 ? from ? = 11.6 ? in the original soil or there was an increase amounted to 41.41% and for the c value, namely c = 9.75 kg/cm2 from c = 1.6 kg/cm2 in the original soil or an increase of 83.59%. The carrying capacity of soil tends to be greater after mixing cement additives. The maximum soil bearing capacity occurs when mixing 8.5% cement with nine days of curing, namely 66,458 t/m2 from 4,696 t/m2 of the original soil capacity or 92.93% for the Terzaghi method. Meanwhile, for the Meyerhoff Method, the maximum soil bearing capacity occurs when mixing 8.5% cement with nine days of curing, namely 92,696 t/m2 from 7,526 t/m2 of the original soil permit carrying capacity of 91.88%.